Classroom discourse in lower secondary French-as-a-foreign-language classes in Norway: Amounts and contexts of first and target language use. (October 2020) - Vold, Eva Thue; Brkan, Altijana
Abstract: This article investigates amounts and contexts of target language (TL) use by teachers and pupils in French-as-a-foreign-language classrooms in Norway, an educational context in which a communicative approach to language teaching is prescribed but target-language-only teaching has not been the prevailing idea. A total of 45 video-recorded French lessons from the last two years of lower secondary school were analyzed for language use and instructional activities. In most classrooms, the L1 was the language of instruction. TL use was restricted to speaking exercises, greetings, and vocabulary instruction and did not seem to increase with class level. The findings diverge in many respects from those in previous research conducted in other educational contexts. By adding data from an under-researched context to the existing body of knowledge, the present study nuances the debate on L1 use in second and foreign language learning and thus the recommendations for classroom practice commonly found in the literature. It also outlines a detailed methodological framework that can be adopted in future studies to obtain data that are comparable across contexts.